Medición financiera y modelos de predictibilidad para el sector automotriz - García Pianda, Ernesto Joel (2022)
The general objective of this work was to develop financial mediation and bankruptcy predictability models through the use of financial statements in order to forecast broken banking risks due to possible consequences generated by the pandemic known as COVID 19. The methodology consisted of a mixed approach since quantitative data were used for the development of financial indicators and the analysis of structure and trend, likewise, it was qualitative because the data was interpreted and criteria of experts in the field were collected. While the type of research was descriptive and explanatory, given that the financial effects generated by the pandemic are described and the casuistries were determined through the opinions of the experts, as well as it is documentary, since relevant information was obtained in prestigious journals, as well as the use of financial statements. As for the method, it is inductive, since the research leads to a qualitative hypothesis, that is, it has an-idea to defend. The techniques used were the interview addressed to 2 managers of the company AutoCredi S.A., and 8 experts from the automotive sector as a complement to strengthen this research. The results showed that there is a lack of knowledge about the models of prediction of bankruptcy and much of it uses comparisons with the sector and the competition, likewise, they mentioned that the pandemic caused a drop in sales. In the realization of financial mediation and predictability models, I show that both the sector and the company are stable in their finances, but compared to previous years, these data have a downward trend. For this reason, it is concluded that companies belonging to this sector use incentive measures to maximize their sales, aswell as apply the models of Altman Z-Score 2, Fulmer H-Score and CA-Score as an indicator for decision making.